2016
DOI: 10.1002/cjce.22491
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and velocity profiles of sediment‐water mixtures using the drift flux model

Abstract: In this paper, the concentration and velocity profiles of sediment water mixtures for open-channel flows are modelled numerically and validated with experimental results. A continuum approach, the drift flux model, is used. The mixture consists of volume fractions with different particle sizes. Hindered settling is taken into account with the closure relation of Richardson and Zaki. Transport equations are used for sediment transport. Turbulence is modelled with the LES (large eddy simulation) WALE model. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Model [16], might be interpreted as a simplified formulation of the two-fluid approach, which is valid under the hypothesis that the particles are rapidly accelerated to their terminal velocity. This assumption is called "local equilibrium approximation" and, broadly speaking, is acceptable if the particles are sufficiently fine.…”
Section: Introductionmentioning
confidence: 99%
“…Model [16], might be interpreted as a simplified formulation of the two-fluid approach, which is valid under the hypothesis that the particles are rapidly accelerated to their terminal velocity. This assumption is called "local equilibrium approximation" and, broadly speaking, is acceptable if the particles are sufficiently fine.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the Mixture Model has recently been coupled with more complex turbulence models such as the LES (Large Eddy Simulation) WALE model [168]. In this study, the numerical description of transport of unsteady sediment-water mixtures, with different particle diameters, in an open channel (tilting flume) is shown to be able to match experimental data with a high degree of accuracy for low and high particle concentrations, but with a less favorable agreement for intermediate particle concentrations.…”
Section: Studies Using the Mixture Modelmentioning
confidence: 99%
“…with exponent α equals to unity. Limitations of this Rouse-type formulation have been evidenced by the measurements of Sumer et al [27], Greimann and Holly [9], Jha and Bombardelli [10], Kironoto and Yulistiyanto [28], and Goeree et al [16]. Owing to its derivation from diffusion theory, the Rouse formula provides a single-phase approach focusing on the sediment particles.…”
Section: Models Reviewmentioning
confidence: 99%
“…Within the field of sediment profiling a range of mathematical concepts has been adopted to predict the concentration profile. Goree et al [16] used continuum theory and incorporated the effect of drift flux due to flow turbulence implemented using large-eddy simulation. However, it was found that the computed results were less accurate in the near-wall region (also agree with [17,18]).…”
Section: Introductionmentioning
confidence: 99%